Baroreflex modulation of muscle sympathetic nerve activity at rest does not differ between morning and afternoon - Hissen, Sarah L.; Macefield, Vaughan G.; Brown, Rachael; Witter, Trevor; Taylor, Chloe E. (Frontiers in Neuroscience, 2015)
The incidence of cardiovascular events is significantly higher in the morning than other times of day. This has previously been associated with poor blood pressure control via the cardiac baroreflex. However, it is not known whether diurnal variation exists in vascular sympathetic baroreflex function, in which blood pressure is regulated via muscle sympathetic nerve activity (MSNA). The aim of this study was to compare vascular sympathetic baroreflex sensitivity (BRS) in the same participants between the morning and afternoon. In 10 participants (mean age 22 ± 2.9 yrs), continuous measurements of blood pressure, heart rate and MSNA were made during 10 minutes of rest in the morning (between 9:00 and 10:00am) and afternoon (between 2:00 and 3:00pm). Spontaneous vascular sympathetic BRS was quantified by plotting MSNA burst incidence against diastolic pressure (vascular sympathetic BRSinc), and by plotting total MSNA against diastolic pressure (vascular sympathetic BRStotal). Significant vascular sympathetic BRSinc and vascular sympathetic BRStotal slopes were obtained for 10 participants at both times of day. There was no significant difference in vascular sympathetic BRSinc between morning (-2.2 ± 0.6 %bursts/mmHg) and afternoon (-2.5 ± 0.2 %bursts/mmHg; P=0.68) sessions. Similarly, vascular sympathetic BRStotal did not differ significantly between the morning (-3.0 ± 0.5 AU/beat/mmHg) and afternoon (-2.9 ± 0.4 AU/beat/mmHg; P=0.89). It is concluded that in healthy, young individuals baroreflex modulation of MSNA at rest does not differ between the morning and afternoon. The results indicate that recording MSNA at different times of the day is a valid means of assessing sympathetic function.